Da educação superior para o mundo do trabalho: perspectivas de pessoas com deficiência - Miranda, Bruna da Silva Ferreira (2019)
The objective of this study was to analyze the perspectives of people with disabilities in the phase of completion of Higher Education, regarding Social / Professional Inclusion in the process of transition from the academic environment to the organizational environment of the world of work. Based on the research line: Cultural, spatial and temporality diversity, chosen to support the study, approaches related to culture, space and time were presented, through analysis of aspects about the production process, acceptance and cultural refusals. The justification was the incipience of studies that signal the transition phase from Higher Education to the world of work, of people with disabilities, that is, the transposition of Academic Inclusion for Social / Professional Inclusion. The baseline in theoretical references, through the specialized literature, was anchored in Prigogine (1994), Mazzotta (1996), Valle (2000), Lancillotti (2003), Matos (2006), Sassaki (2006), Beyer (2010), Meihy and Holanda (2013), Turchiello and Machado (2015), in the Public Policies of Inclusion and in publications of the Ministry of Labor and Employment (2015). The field research considered the qualitative methodology, based on the conceptions of André (2009) and proposed, through the concepts of Meihy and Ribeiro (2011) and Meihy and the Netherlands (2013), to present the study using thematic oral history with elements of (Meihy and Ribeiro, 2011) and Meihy and the Netherlands (2013). The analysis of the data included the practices of transcription, textualization and transcriation, anchored in Meihy and Ribeiro (2011). Finally, validation was carried out, in which the text produced through the dialogue was conferred from the first contact, and possible errors and mistakes of the transcription were verified and corrected. In this phase, this work of interaction was legitimated in a non-hierarchical way and the possibility of producing knowledge from the generated document was validated. In analyzing the narratives, it was possible to note that the deficiency and the limitations presented by the collaborators were not decisive and, much less, impediment barriers, with respect to the presented perspectives and the established personal, academic and professional objectives. Each narrative analyzed, each report of experience transcribed and interpreted, showed the courage and determination of all to overcome the limitations and to conclude Higher Education. On the other hand, this study also showed what employees think about the society's view of people with disabilities. The untiring struggle to demonstrate overcoming, goes to prove to itself how much they are able, but mainly, to show to society that people with disabilities exceed limits.